2022
DOI: 10.1101/2022.01.11.475943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular brake that modulates spliceosome pausing at detained introns contributes to neurodegeneration

Abstract: Emerging evidence suggests that intron-detaining transcripts (IDTs) are a nucleus-detained and polyadenylated mRNA pool for cell to quickly and effectively respond to environmental stimuli and stress. However, the underlying mechanisms of detained intron (DI) splicing are still largely unknown. Here, we suggest that post-transcriptional DI splicing is paused at Bact 29 state, an active spliceosome but not catalytically primed, which depends on SNIP1 (Smad Nuclear Interacting Protein 1) and RNPS1 (a serine-rich… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…We found that moderate depletion of U2 snRNA levels changed splicing order in many genes. Interestingly, when we reanalyzed nanopore sequencing data from the cerebella of U2 snRNA mutant ( NMF291 -/- ) mice 48 , we found a similar co-occurrence of RIs and SEs (Extended Data Fig. 5G-H), indicating that splicing order is partially determined by the spliceosome and that splicing fidelity is disrupted when splicing order changes in vivo .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that moderate depletion of U2 snRNA levels changed splicing order in many genes. Interestingly, when we reanalyzed nanopore sequencing data from the cerebella of U2 snRNA mutant ( NMF291 -/- ) mice 48 , we found a similar co-occurrence of RIs and SEs (Extended Data Fig. 5G-H), indicating that splicing order is partially determined by the spliceosome and that splicing fidelity is disrupted when splicing order changes in vivo .…”
Section: Discussionmentioning
confidence: 89%
“…F) Distribution of the number of reads with SE, RI, both or neither in direct RNA sequencing data from control or U2 snRNA KD, for all the genes included in the SE and RI co-occurrence analysis shown in Figure 4D. G) Number of genes showing co-occurrence of SE(s) and RI(s) in transcriptome-wide cDNA-PCR nanopore sequencing data from WT and NMF291 -/- (U2 snRNA mutant) mice 48 . The x-axis categories are the same as in Figure 4D.…”
Section: Extended Data Figure 1 (Related To Figure 1)mentioning
confidence: 99%